2012
DOI: 10.1063/1.4737210
|View full text |Cite
|
Sign up to set email alerts
|

Snap-in dynamics of single particles to water drops

Abstract: The interaction between solid particles and gas-liquid interfaces is relevant in technological applications. Former studies did focus on detachment-dynamics of particles from thin liquid films or on attachment-dynamics of particles to gas bubbles. Here, we investigated snap-in dynamics of individual micron-sized particles to water drops by means of the colloidal probe technique. The snap-in time (∼0.1 ms) and the snap-in force of hydrophilic and hydrophobic particles were measured. The snap-in time increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Variability may also arise from the dynamic nature of wetting. Initially, the capillary forces and hydrodynamics of a particle adsorbing to a fluid-fluid interface give wetting speeds in the order of a few m/s, while also longer timescale relaxation processes are observed with speeds as low as 10 À3 mm/s [38][39][40]. Such dynamic wetting effects should be taken into account when extracting values for the contact angle.…”
Section: Experimental Techniques For Measuring the Contact Angle Of Pmentioning
confidence: 97%
See 2 more Smart Citations
“…Variability may also arise from the dynamic nature of wetting. Initially, the capillary forces and hydrodynamics of a particle adsorbing to a fluid-fluid interface give wetting speeds in the order of a few m/s, while also longer timescale relaxation processes are observed with speeds as low as 10 À3 mm/s [38][39][40]. Such dynamic wetting effects should be taken into account when extracting values for the contact angle.…”
Section: Experimental Techniques For Measuring the Contact Angle Of Pmentioning
confidence: 97%
“…A description based on capillary forces and hydrodynamics results in exponential relaxation times with typical timescales of ms. Recently much longer timescales -several minutes, hours -were measured [38][39][40]. These observations call for the development of methods to quantify and model dynamic wetting effects on individual particles over a broad range of time and energy scales, and suitable for a wide range of particle types and fluid properties.…”
Section: Particles At Fluid-fluid Interfaces: Dynamic Wettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the dynamics of attachment (snap in) or detachment was studied in more detail. When a particle with a diameter of the order of 100 lm snaps in at the interface of a low viscosity-liquid such as water and a gas, its dynamics is usually governed by the interplay of capillary and inertial forces [14]. For particles attaching to liquid/liquid interfaces, the fast initial dynamics may be followed by an extremely slow process (on a time scale of days or even months) during which the particle assumes its final configuration at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results are consistent with a growing body of work showing -in the same, indirect way -that nanoscale heterogeneities do exist in colloids and are important for understanding their behaviour at fluid interfaces. In fact, recent experiments have shown that the attractive interactions between particles at interfaces 6 , as well as the relaxation rates of particles that breach an interface 7,8 , appear to be governed by surface defects. And because colloids typically have surface groups that keep the particles from aggregating, surface defects and contact-line pinning may be inherent features of colloidal systems.…”
Section: Vinothan N Manoharanmentioning
confidence: 99%